Ganz unverhofft an einem Hügel sind sich begegnet Fuchs und Igel… - Strozyk, Andreas (Staatlicher Kunsthandel der DDR, 1982)
White poster; reproduction of story about fox and hedgehog by Wilhelm Busch, with colour illustration at the centre PO-0193